Interfacial engineering of a ZnO electron transporting layer using self-assembled monolayers for high performance and stable perovskite solar cells - Han, Jinyoung; Kwon, Hannah; Kim, Eunah; Kim, Dong-Wook; Son, Hae Jung; Kim, Dong Ha (Journal of materials chemistry. A, Materials for energy and sustainability, 2020)
We developed perovskite solar cells (PSCs) with a ZnO electron-transporting layer (ETL) of which the surface was passivated with methoxybenzoic acid self-assembled monolayers (SAMs). The self-assembled monolayer (SAM) simultaneously improved the photovoltaic performance and device stability. First, the methoxybenzoic acid, which is noncovalently bonded to the methylammonium of the perovskite layer, effectively induced dipole moments; in particular, 3,4,5-trimethoxybenzoic acid (TMBA) gave a larger workfunction shift of ZnO ETL compared with 4-methoxybenzoic acid (MBA) and 3,4-dimethoxybenzoic acid (DMBA) owing to its strong dipole moment and hydrogen-bonding between the methoxy group and ammonium. This effectively enhanced the built-in voltage of the perovskite solar cell (PSC) device, which resulted in an improved electron transfer from the active layer to the ETL and a higher open-circuit voltage. Secondly, the SAM layer controlled the wettability of the perovskite precursor solution on the ZnO ETL and significantly improved the crystalline properties of the perovskite layer. Moreover, the ZnO/SAM ETL remarkably increased the PSC device stability under ambient conditions by preventing the proton transfer reaction between the perovskite layer and the ZnO ETL. As a result, the TMBA-SAM based PSC device achieved a significantly enhanced efficiency of 13.75% compared to 1.44% for the bare ZnO with high long-term stability. The SAM layer which formed hydrogen-bonding to the methylammonium of the perovskite induced dipole moments at the interface, resulting in energy band bending and increased built-in voltage, and consequently, improved charge transfer of the PSC.